STUDY OF QUALITY CONTROL ON TUNA LOIN CENTER CUT FROZEN PRODUCTION USING THE SIX SIGMA METHOD IN “X” TUNA FREEZING COMPANY - Muh Suryono; Sumartini Sumartini; Rahadatul Aisy (Politeknik Kelautan dan Perikanan Dumai, 2023)
Fishing companies must achieve the target by producing quality products, namely producing products according to predetermined standards, one of the efforts that can be done is to carry out quality control, many quality control methods can be applied, one of which is six sigma. The purpose of this study is to examine and apply quality control tools and provide alternative solutions or proposed improvements to reduce product defects inTuna Loin CutCenter Frozen. The method used in this study of quality control uses the Six Sigma method using the DMAIC method of analysis. The processing process of Tuna Loin CutCenter Frozenat the Tuna X Freezing Company. The results obtained are 6characteristics Critical to Quality with a DPMO value of 4,999,165 and the sigma value of 4.075887 in January 2020-February 2021. From the results of FMEA obtained 3 causes with the highest RPN value obtained from 3 defects, namely packaging vacuum leaking, uneven CO gas andengine program metalerrors. The suggested improvements are making a logbook to check the condition of the machine regularly, making a checklist to carry out tighter supervision of employees and calibrating the program by QC every time they do packing. After carrying out thestage control, the DPMO value added is 212.560 and Sigma is 5.023978. So it can be concluded that the application of themethod six sigma as a quality control control can reduce the DPMO value by 12.75%.